A presença/ausência do índio na pós-graduação da Universidade Federal de Sergipe : entre tensões e o direito de seguir além da aldeia - Ferro, Larissa Ferreira (2018)
This work aims to understand, from the legislations, decrees, ordinances, regiments, normative acts and other UFS documents related to the object, which is the place of the indigenous within of this University, using the words of the indigenous people themselves. At all times the indigenous person occupies the center of the stage, understanding him as an active subject of all his historical, social and educational process. In every (re) corner of this world he keeps his "fingerprint" and the mark of his "heel at the top of the skyscrapers.". Understanding that the university spaces also belong to the natives is the motto and the end of the present work. The indigenous is its main subject. Subject of rights. Subject and author of an open field of discussion, research, discoveries, achievements. This is a qualitative research based on the case study method and used semi-structured interviews with indigenous people and a representative of the University elected for the present study. The theoretical framework is based on the concepts of dialogism, polyphony and presumed present in works Bakhtinian (2002, 2005, 2006, 2009, 2012, 2013), in the ideas of Vygostsky, on Marx's ontological and socio-historical assumptions, on the concept of Praxis addressed by Vásquez and on the critical speech analysis, from Fairclough's (2001) studies. It starts from the idea that the UFS is in process of recognition of these minority groups that are beginning to be present in their spaces. The results show that the UFS is not yet open to the minorities that enter their walls, although it has recently approved the affirmative action policy at a meeting of the Teaching, Research and Extension Council (CONEPE). The major problem, however, refers to the lack of funding that guarantees the access with permanence and conclusion. It was also observed that both the demand and the interest of the native to attend a postgraduate course exist. The lack, however, of guidence and funding, of a university that contemplates the specificities of the indigenous culture in its curricular matrix, becomes a barrier to the inclusion of the indigenous in this stage of formation, which shows that their place is still (in) visible not to say shy, petty or even (non) existent.